2009
DOI: 10.3941/jrcr.v3i3.153
|View full text |Cite
|
Sign up to set email alerts
|

Spinal MRI Findings of Guillain-Barré Syndrome

Abstract: Guillain-Barré syndrome is a relatively common, acute, and rapidly progressive, inflammatory demyelinating polyneuropathy. The diagnosis is usually established on the basis of symptoms and signs, aided by cerebrospinal fluid findings and electrophysiologic criteria. Previously, radiologic examinations have been used only to rule out other spinal abnormalities. We report a case of systemic lupus erythematosus associated with Guillain-Barré syndrome with marked enhancement of nerve roots of the conus medullaris … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
32
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 4 publications
2
32
2
2
Order By: Relevance
“…[1][2][3] A mild respiratory or gastrointestinal tract infection precedes onset of symptoms in 75% of patients with GBS. 4,5 It has been suggested that surgical procedures, lymphoma, and systemic lupus erythematosus may also be predisposing conditions for GBS. 4 Presentation of GBS is initially characterized by progressive and ascending weakness of the extremities and areflexia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] A mild respiratory or gastrointestinal tract infection precedes onset of symptoms in 75% of patients with GBS. 4,5 It has been suggested that surgical procedures, lymphoma, and systemic lupus erythematosus may also be predisposing conditions for GBS. 4 Presentation of GBS is initially characterized by progressive and ascending weakness of the extremities and areflexia.…”
mentioning
confidence: 99%
“…4,5 It has been suggested that surgical procedures, lymphoma, and systemic lupus erythematosus may also be predisposing conditions for GBS. 4 Presentation of GBS is initially characterized by progressive and ascending weakness of the extremities and areflexia. Progression of symptoms is rapid and may include sensory disturbances, facial nerve palsies, autonomic dysfunction, pain, numbness, paraesthesia, and respiratory failure.…”
mentioning
confidence: 99%
“…However, there are several reports of that enhanced spinal MR imaging can be used as a supplementary diagnostic modality in the diagnosis of GBS, when the clinical and electrophysiologic findings are equivocal12). The presence of nerve root enhancement on enhanced spinal MRI can be the evidence of GBS, in the present case.…”
Section: Discussionmentioning
confidence: 55%
“…The high spatial resolution and excellent soft‐tissue contrast of MRI facilitates identification of structural nerve abnormalities caused by traumatic injury or repetitive stress . The fluid sensitivity of MRI provides detection of edema in nerves potentially caused by various pathologic mechanisms including inflammation, ischemia, and autoimmune disease . Quantitative mapping of diffusion, T2, and magnetization transfer demonstrated promising results in monitoring nerve degeneration …”
mentioning
confidence: 99%
“…2,3,8,10 The fluid sensitivity of MRI provides detection of edema in nerves potentially caused by various pathologic mechanisms including inflammation, 11 ischemia, 12,13 and autoimmune disease. 14,15 Quantitative mapping of diffusion, T2, and magnetization transfer demonstrated promising results in monitoring nerve degeneration. 9,16,17 MRI evaluation of nerve fascicular structures, however, has not been reliable because of the limited resolution on the widely used 1.5T or 3T MRI scanners.…”
mentioning
confidence: 99%